Simultaneous measurement of temperature and concentration during faceted cellular array growth under microgravity. (1st March 2014) - Inatomi, Yuko; Ashida, Motohiro; Sakata, Kaoruho; Okutani, Takeshi
Abstract : The authors performed FACET (Investigation on Mechanism of Faceted Cellular Array Growth) experiments under long duration microgravity on the International Space Station (ISS) in 2010. The temperature and concentration distributions in the melt during the growth were precisely measured with high spatial resolution. Negative temperature gradient as well as negative concentration gradient ahead of the S/L interface can be expected to be the driving forces of the morphological instability. It is evident that the conventional model based on the frozen temperature approximation is insufficient to explain the growth mechanism of the faceted cellular array.